Evaluation of body image and self-concept and their correlation with depressive symptoms in Parkinson's disease Avaliação da imagem corporal, autoconceito e suas correlações com os sintomas depressivos na doença de Parkinson - Ariane Haydée Estrada Gamarra; Cibele Silva Molski; Arlete Hilbig; Cristina Kern Valentini; Vera Lúcia Widniczck Striebel; Carlos Roberto de Mello Rieder (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To identify characteristics of body image and self-concept in individuals over fifty years of age with Parkinson's disease (PD). The secondary objectives are to analyze whether body image and self-concept are influenced by the severity of PD and to verify if there is correlation between depression, self-concept and body image in cases of PD. METHOD: Participating in the study were 48 individuals, being 26 with PD and 22 Controls. The instruments used were: The Mini Exam of Mental State, The My Body Image Test, The Factorial Self-concept Test, The Beck Depression Inventory, the motor section of The Unified Parkinson's Disease Rating Scale and The Modified Hoehn and Yahr Scale. RESULTS: In PD the perception of body image and self-concept demonstrated significantly reduced values p<0.001 and p=0.012 respectively, and the presence of depression symptomatology was significantly more (p=0.002). CONCLUSION: Individuals with PD present alteration of body image and self-concept and also present lower personal confidence and lower social receptivity, correlated with depressive symptoms. OBJETIVO: Identificar características de imagem corporal e autoconceito em indivíduos com doença de Parkinson (DP) acima de cinqüenta anos de idade. Os objetivos secundários são analisar se a imagem corporal e o autoconceito são influenciados pela gravidade da DP e, verificar se existe correlação entre depressão, autoconceito e imagem corporal na DP. MÉTODO: Participaram do estudo 48 indivíduos, sendo 26 com DP e 22 Controles. Os instrumentos utilizados foram: Mini-Exame do Estado Mental, Teste A Minha Imagem Corporal, Escala Fatorial de Autoconceito, Inventário de Depressão de Beck, Unified Parkinson's Disease Rating Scale parte motora e Hoehn e Yahr Modificada. RESULTADOS: Na DP a percepção da imagem corporal e do autoconceito, demonstraram valores reduzidos significativamente (p<0.001 e p=0.012) respectivamente, e a sintomatologia depressiva apresentou-se significativamente maior (p=0.002). CONCLUSÃO: Indivíduos com DP apresentam alteração da imagem corporal e do autoconceito, apresentaram também menos confiança pessoal e menor receptividade social correlacionados com sintomas depressivos.